Observations on two microbial life strategies in soil: Planktonic and biofilm-forming microorganisms are separable. (September 2019) - Bystrianský, Lukáš; Hujslová, Martina; Hršelová, Hana; Řezáčová, Veronika; Němcová, Lenka; Šimsová, Jana; Gryndlerová, Hana; Kofroňová, Olga; Benada, Oldřich; Gryndler, Milan
Abstract: Biofilms, the communities of sessile microbial forms, are hotspots of biological activity that coexist in soil together with free-living (planktonic) biota. Sessile and planktonic microbial communities may constitute functionally different groups of organisms with different roles in interactions with organic matter and plants. Nevertheless, soil microbiomes are regularly analyzed without distinguishing biofilm inhabitants and planktonic organisms. Consequently, basic information regarding taxa constituting both communities is severely lacking, which limits the understanding of the basic structure of soil microbiome and consequently also of the microbiome functioning. In this study, we tested the hypothesis that soil biofilm and planktonic microbial communities are different. Glass fiber filters were exposed to three different field soils for 12 weeks and biofilms arose on their surfaces. The biofilms were further separated from the planktonic forms by washing the latter out of the filters and both communities were analyzed using next generation sequencing. The results revealed significant differences between biofilm and planktonic communities of bacteria and eukaryotic organisms. Our data indicate common production of motile microbial cells in the soil and specialization of some taxa ( Legionella spp.) to planktonic life mode. We also noted an association between the abundance of some bacterial taxa and eukaryotic grazers suggesting a trophic interaction. Tillage, as a cause of soil disturbance, did not result in a significant increase in the abundance of most abundant biofilm associated microbial taxa. This is the first analysis of separated sessile (biofilm) and motile (planktonic) communities of soil microorganisms. Highlights: Soil biofilm and planktonic microbial communities differ significantly. Many soil microorganisms occur both in planktonic and biofilm communities. Association between some biofilm bacteria and eukaryotic grazers was noted. Tillage did not affect the abundance of main biofilm associated bacteria.